Propuesta de un nuevo Código de ética para los servidores públicos del Estado de Nuevo León = Proposal of a new code of ethics for the public servants of Nuevo León. - Jiménez Gómez, Enrique; Badii Zabeh, Mohammad Hosein (Universidad Autónoma de Nuevo León, 2007)
Abstract. The global society of the XXI century has a crisis of values. The only important thing is the money. This is serious and dramatic when this crisis is presented in the public service because it interests to the whole society that needs a program of values that it serves from foundation to government's action. This program of values is a Code of Ethics in the public Administration that here intends.